Three-dimensional thermal modelling of transformers in transformer room for spatial and temporal failure analysis - Tao, Wang (2018)
Temperature is a key factor for failure analysis of power transformers. Conventionally, transformer failure rate is calculated with hot spot temperature induced from IEEE empirical equations. This article firstly introduces a spatial and temporal related failure model based on three-dimensional thermal simulations of transformer and the related environment. The proposed thermal model is established with computational fluid dynamics for ventilation calculation and heat generation equations for power device simulation. Cooling strategies and mutual heating effect of power equipment are considered for an accurate temperature distribution prediction. By incorporating the three-dimensional thermal model into the service life-dependent and temperature-dependent model, the failure rate of each spatial point in power transformer could be calculated according to Arrhenius theory and Weibull distribution. The simulation results show that the proposed model clearly improves the accuracy of failure analysis and can be used for thermal and ventilation design of transformer room.